Dynamics and diversity of cultivable rhizospheric and endophytic bacteria during the growth stages of cilembu sweet potato (Ipomoea batatas L. var. cilembu) - Tangapo, Agustina Monalisa; Astuti, Dea Indriani; Aditiawati, Pingkan (Agriculture and Natural Resources, 2018)
Cultivable rhizospheric and endophytic bacteriawere isolated from cilembu sweet potato during the 5 mth period post planting to assess the diversity and dynamics of its bacterial community. The number of colony forming units of rhizospheric bacteria was significantly higher than for the endophytic bacteria. The diversity and genera richness of the bacteria associated with cilembu sweet potato in the early stages of growth were higher than in the last stages. The different cultivable bacteria were identified using 16S rRNA gene sequencing as: Alphaproteobacteria (Methylobacterium, Sphingomonas, Paracoccus), Gammaproteobacteria (Klebsiella, Enterobacter, Pseudomonas, Serratia), Bacteroidetes (Chryseobacterium, Sphingobacterium), Firmicutes (Exiguobacterium, Bacillus, Staphylococcus) and Actinobacteria (Streptomyces, Arthrobacter, Kocuria, Microbacterium, Micrococcus). The nitrogen content in the soil may significantly affect the change of bacterial diversity in the rhizosphere during the growth of cilembu sweet potato. All isolates were capable of producing plant growth-promoting traits, alone or in combination, such as indole acetic acid production, phosphate solubilization, ammonia production, nitrogen fixation, cellulolytic and amylolytic activity.